2017
DOI: 10.3727/096368916x693022
|View full text |Cite
|
Sign up to set email alerts
|

Active Subjects with Autoimmune Type 1 Diabetes have Better Metabolic Profiles than Sedentary Controls

Abstract: Previous studies in humans with type 1 diabetes mellitus (T1D) and in nonobese diabetic mice have investigated the beneficial immunomodulatory potential of aerobic physical activity. Performing high volume of aerobic exercise may favorably regulate autoimmunity in diabetes. We tested whether increased physical activity is a self-sufficient positive factor in T1D subjects. During a 3-month observational period, active (six males; 40.5 ± 6.1 years; BMI: 24.5 ± 2.1) and sedentary (four males, three females; 35.9 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
22
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(23 citation statements)
references
References 32 publications
1
22
0
Order By: Relevance
“…Event in the management of T1D, omni-comprehensive programs are capable to optimize and maintain positive metabolic outcomes, also assisted by telemedicine and diversified telehealthcare systems [74,83,84].…”
Section: Comprehensive Educational Programs In the Management And Carmentioning
confidence: 99%
“…Event in the management of T1D, omni-comprehensive programs are capable to optimize and maintain positive metabolic outcomes, also assisted by telemedicine and diversified telehealthcare systems [74,83,84].…”
Section: Comprehensive Educational Programs In the Management And Carmentioning
confidence: 99%
“…In adults with T1D, we have conducted several studies showing the multifaceted positive effects of exercise on immunometabolism and autoimmunity [8,74,126,127].…”
Section: After Normalizing Bmi Diet Age Estaki Et Al Analyzed Fecmentioning
confidence: 99%
“…In other longitudinal studies (observational and intervention) we showed that exercise may positively modulate immune system function in β-cells transplanted recipients. Active subjects with T1D, following islet transplantation (IT), exhibited ameliorated scores of disease management, quality of life [5], metabolic control, body composition [6]. In addition, in IT subjects, physical exercise was capable to counteract diabetic symptoms and mitigated the side effects of immunosuppressive drugs and graft dysfunction [7,8].…”
Section: Immunomodulatory Indications From Animal and Human Modelsmentioning
confidence: 99%
“…Likewise for individuals with T2D, physical activity should be embodied in the management of T1D as it increases insulin sensitivity (both short and long term), lowers blood glucose levels, reduces body fat (and ameliorates body mass composition [6]), improves cardiovascular function. However, due to the loss of the β-cell pancreatic mass and/or -function, subjects with T1D uniquely face a number of challenges in preparation for, during, and after each session of exercise.…”
Section: Exercise In T1d: the Risk-benefit Analysismentioning
confidence: 99%
See 1 more Smart Citation